How can virtuous real estate public-private partnerships be developed? Towards a co-evolutionary perspective. (December 2020) - Abatecola, Gianpaolo; Mari, Michela; Poggesi, Sara
Abstract: How can virtuous real estate Public-Private Partnerships (PPPs) be developed? This question appears buoyant in urban planning. In fact, notwithstanding their increasing appeal for governing the current complexity of urban infrastructure projects, evidence from the PPP practice is still controversial; some PPPs appear virtuous (i.e. value generating for the parties involved), while some others do not. This is why understanding their conceptual nature is currently posited, by both scholars and policy makers, as a major knowledge gap. To fill this gap, in this conceptual article we adopt a co-evolutionary perspective. We argue co-evolution can provide an innovative, valuable contribution to the study of PPPs. In particular, its most vivid identity can produce a joint and dynamic analysis of the reciprocal, behavioral interdependencies between the PPP elements, such as the private and public counterparts involved in a PPP project. On this basis, we first develop a 2-stage conceptual framework about the potential birth and development of a PPP. We then provide a case illustration of the framework through commenting on the recent construction, and actual functioning, of the Benito Stirpe Football Stadium in the town of Frosinone (Italy). Implications for research and urban policy making follow. Highlights: How to develop virtuous real estate PPPs is a buoyant question in urban planning. To address this question, in this conceptual article we adopt a co-evolutionary perspective. Our 2-stage theoretical framework regards the potential birth and development of a PPP. The framework illustration focuses on the Benito Stirpe Football Stadium (Frosinone, Italy). Implications for research and urban policy making follow